CHROMATOGRAPHIC ANALYSIS OF SOME ANTIBIOTICS IN WATER AND SEDIMENT SAMPLES COLLECTED FROM THE ROMANIAN TISZA RIVER WATERSHED - COMAN, Virginia; BELDEAN-GALEA, Simion; COPACIU, Florina; VLASSA, Mihaela; FILIP, Miuţa (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Antibiotics are natural or semi-synthetic compounds used for many decades in human, veterinary and plant medicine to prevent and/or to treat bacterial infections and also to promote productivity in animal farming. Traces of antibiotics are found in waste, surface and ground waters, the main source of water pollution being considered waste waters from the industrial production, hospitals, livestock farms, households and incompletely metabolized drugs. The uncontrolled input of antibiotics in surface waters can lead to some unexpected health effects and to an increased resistance to these drugs. The aim of this work consists in the monitoring of six antibiotics (Ampicillin, Amoxicillin, Penicillin G, Ceftazidime, Tetracycline and Doxycycline) in river waters and sediment samples from the Romanian Tisza River Watershed. Solid-phase extraction (SPE) on Oasis HLB Waters cartridges was used for the isolation of antibiotics from water matrices and ultrasound-assisted extraction (USAE) followed by SPE for the sediment samples. Then, the antibiotics were analysed by high-performance liquid chromatography coupled with diode array detector or mass spectrometer (HPLC-DAD/MS). The developed SPE/USAE-HPLC-DAD/MS procedures were applied to monitor these antibiotics in river waters during thirteen months and to analyze them in some sediment samples. The obtained results showed the presence of Tetracycline, Doxycycline and Ceftazidime in the investigated samples.